talabalarning axborot kompetentligini takomillashtirishning ba’zi masalalari - Karlibaeva, G.E.; Matjanov, N.S. (SCIENCE and SOCIETY, 2023)
The article deals with the theoretical issues of improving the information competence of students in the process of teaching physics. Provides information about the importance of didactic principles in improving the information competence of students.
Keywords: information and communication technology; student; information competence; competence; teacher; physics; educational process